2021
DOI: 10.1007/s00423-021-02152-6
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and laparoscopic liver resection—comparative experiences at a high-volume German academic center

Abstract: Purpose Minimally invasive liver surgery (MILS) is a feasible and safe procedure for benign and malignant tumors. There has been an ongoing debate on whether conventional laparoscopic liver resection (LLR) or robotic liver resection (RLR) is superior and if one approach should be favored over the other. We started using LLR in 2010, and introduced RLR in 2013. In the present paper, we report on our experiences with these two techniques as early adopters in Germany. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Clavien-Dindo complications of grade 3 and above occurred in 4-6% of the laparoscopic patients, 0-22% in the robotic cohort and 25-35% in the open cohort and, although this difference was statistically significant only when the LLR was compared to the OLR group, these rates are well within the range published in the literature of 5-55% after laparoscopic hepatectomy, 17-20% after robotic resection and 17-61% after open hepatectomy [33,35,36]. The major cause of morbidity after major liver resection is bile leak with 13.5% of patients after major hepatectomy found to have a bile leak in one study [37].…”
Section: Discussionsupporting
confidence: 75%
“…Clavien-Dindo complications of grade 3 and above occurred in 4-6% of the laparoscopic patients, 0-22% in the robotic cohort and 25-35% in the open cohort and, although this difference was statistically significant only when the LLR was compared to the OLR group, these rates are well within the range published in the literature of 5-55% after laparoscopic hepatectomy, 17-20% after robotic resection and 17-61% after open hepatectomy [33,35,36]. The major cause of morbidity after major liver resection is bile leak with 13.5% of patients after major hepatectomy found to have a bile leak in one study [37].…”
Section: Discussionsupporting
confidence: 75%
“…Nineteen studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] elucidated the outcomes of robotic and laparoscopic surgery, with 682 and 1101 patients, respectively. The characteristics of studies included in the meta-analysis are shown in ( Table 1 and Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the authors state that in Taiwan, costs for inpatient care are lower, because of the national reimbursement system, thus overshadowing the cost-benefit of shorter LOS, negatively affecting the total costs of RLR compared to nations spending more money on inpatient care [ 87 ]. In Germany, the healthcare system predefines the postoperative stay for reimbursement, thus influencing total costs [ 88 ].…”
Section: Costsmentioning
confidence: 99%